Kalimantan Barat sebagai ‘Daerah Perbatasan’: Sebuah Tinjauan Demografi-Politik - Riwanto Tirtosudarmo (Antropologi Indonesia, 2002)
This paper, using a political demography perspective, attempts to reconstruct the perception of the center on the borderland of West Kalimantan and Sarawak, Malaysia. Basically there are two important views that dominating the center's perception on the borderland: 'perceived economic advantage and perceived threat'. Based on these twofold perceptions, policies and programs were implemented to serve the political and economic interests of the center. These policies and programs have generally resulted in the marginalization of border's people livelihood. Among the crucial policies that significantly changed the social and cultural dynamics of the local population is the transmigration program and the village enlargement project. These two programs represent the center's demographic engineering policy deeply rooted in the perception that the border areas should be militarily secured from various threats from abroad. The current moves toward regional autonomy and decentralization will likely provide new avenues for the local population in West Kalimantan to reassert their economic and political aspirations.